Comparison of delta model in the north coast of Central Java using remote sensing techniques (Case study in Delta Comal, Delta Bodri and Delta Wulan). (March 2019) - Sanjoto, T B; Juhadi,; Nugraha, S B
Abstract: There are many deltas that are grown and developed relatively quick in coastal area of North Java. The development of the delta region is characterized by the occurrence of sedimentation processes that cause the emerge land. The sedimentation process in the delta region is influenced by the sediment supply from the erosion of the upstream watershed. The land use change will potentially affect the rate of erosion, resulting in a sedimentation process in coastal areas. This study aimed to compare the morpho dynamic model of Delta on the north java coast used multi-temporal remote sensing techniques, namely 1987, 1992, 1997, 2002, 2007, 2012 and 2017. The study locations were Delta Comal, Delta Bodri and Delta Wulan. This research was descriptive-explanatory, which was trying to find the widest possible data in order to study the dynamics of Delta, as well as trying to explain the relationship between the factors that influence it. In support of the study used Landsat satellite imagery, Indonesia Topographic Map, ER Mapper 7.0 software, GIS Arc, GPS and other equipment. The results showed that the morphodynamical model of the study area varied. At the beginning of its development, all of the three deltas showed the shape of cuspate but subsequently develop into different morphological forms. In Comal Delta originally cuspate, then developed into Lobate, then tends to cuspate again. In Delta Bodri, from cuspate originally developed into Lobate. While, in Delta Wulan originally cuspate developed into foot bird Delta. Based on the change of delta area, for Delta Comal and Delta Bodri tends to increase, while Delta Wulan tends to fluctuate.